A visão de gestores da área financeira acerca do papel da impulsividade na tomada de decisão - Araújo, Beatriz Tenuta (2015)
Decision-making is part of the routine of any person; which may come from simple choices to the most structured ones. In business environments decisions are considered to be rational - however it is possible to notice that often decisions are made based on a subjective list of unclear or illogical selections. In addition, the decision maker is also influenced by the environment to which he/she is inserted, as well as the social interactions related, leading to decision made under uncertain scenarios, via the utilization of simplified "shortcuts" to the choice of the alternatives. Decision can also de triggered by emotions or impulses, responsible for quick and "in the spur of the moment" responses, however known to be uncontrolled, unreasonable and premature - which can be understood as impulsivity. This study aims to identify the role impulsivity plays in decision-making, from the perspective of financial managers, and in the way it can be associated in the development of the decision-making competence. The study is based on the frameworks available for understanding the process from the classical point of view of decision-making based on the concept of "homo economicus", as well as the economic models of decision arising from that: bounded rationality, Theory of Expected Utility and Prospect Theory. Cognitive models of linear and bidimensional decision-making are also listed, providing inputs to "open the black box of decision” via the insertion of the role emotions, affections, behaviors and impulses play in the decision process. The qualitative study applied the non-probability sampling method intended for the data collection of the semi-structured interviews. Five financial managers were interviewed, from fields such as Controllership, Risk, Treasury and Corporate Finance; and the data was further analyzed via the content analysis technique. It was identified positive aspects of impulvisity towards decision-making, from agility and risk propensity standpoints; such as negative aspects associated with the influence of cognitive biases and social influence, over (or under) confidence, conflicts of interest and lack of rationality. Actions focusing on the development of decision-making competences in the light of the impulsive behavior were proposed by managers; subsequentenly leading to suggestions of opportunities for further studies, and the inclusion of behavioral disciplines in the curriculum of undergraduate and graduate studentes in Accounting.